2020
DOI: 10.3390/min10020168
|View full text |Cite
|
Sign up to set email alerts
|

Deep Mineral Exploration of the Jinchuan Cu–Ni Sulfide Deposit Based on Aeromagnetic, Gravity, and CSAMT Methods

Abstract: The exploration of deep mineral resources is an important prerequisite for meeting the continuous demand of resources. The geophysical method is one of the most effective means of exploring the deep mineral resources with a large depth and a high resolution. Based on the study of the geological background, petrophysical properties, and aeromagnetic anomaly characteristics of the Jinchuan Cu–Ni sulfide deposit, which is famous throughout the world, this paper uses the widely used gravity, aeromagnetic, and CSAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Seafloor massive sulphides have significantly higher acoustic impedances than silicate rocks, and as such can be directly interpreted from seismic reflection data provided the deposits meet the geometric constraints required for seismic detection 68 . Additionally, the mounds here are also associated with strong magnetic and gravity anomalies due to their strong magnetic susceptibility and high densities, which could point to the occurrence of mineral deposits 69 71 , while their geometries and architectural elements are akin to the archetypical seafloor mineral mounds reported in many settings 72 and hydrothermal vent complexes observed along many magma-rich margins 64 , 73 , 74 . Therefore, the potential for seafloor mineral/metal deposits should be investigated in the GSB and other basins with similar geological setting.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Seafloor massive sulphides have significantly higher acoustic impedances than silicate rocks, and as such can be directly interpreted from seismic reflection data provided the deposits meet the geometric constraints required for seismic detection 68 . Additionally, the mounds here are also associated with strong magnetic and gravity anomalies due to their strong magnetic susceptibility and high densities, which could point to the occurrence of mineral deposits 69 71 , while their geometries and architectural elements are akin to the archetypical seafloor mineral mounds reported in many settings 72 and hydrothermal vent complexes observed along many magma-rich margins 64 , 73 , 74 . Therefore, the potential for seafloor mineral/metal deposits should be investigated in the GSB and other basins with similar geological setting.…”
Section: Discussionmentioning
confidence: 69%
“…The seafloor mounds, pipes, magmatic sills (intrusive rocks) and volcanoes interpreted in this work are not drilled or sampled. Hence, their interpretations are based on the knowledge of the general geology of the area 85 , history of volcanism and magmatism in southern South Island of New Zealand 33 35 , their marked physical properties, acoustic contrasts relative to their host rocks 69 71 and seismic expressions as observed from other margins 86 , 87 . Additionally, the convex-upwards morphology of some of the paleo craters and mounds at the Eocene levels are cautiously interpreted considering that some of them may be geophysical velocity ‘pull-up’ artefacts.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the advantages of comprehensive geophysical survey methods for detecting concealed metallic ore bodies were fully availed in this study to detect concealed iron ore bodies [15,16]. In particular, owing to their convenience and sensitive response to anomalous bodies, the magnetic and electromagnetic survey-based devices can rapidly determine the anomalous spatial planar locations and anomalous profile distribution patterns of the concealed iron ore bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of gridding-type engineering drilling alone to evaluate the deep and surrounding areas of existing mines is often too costly, and thus impractical, whereas the use of older monotonous aeromagnetic and gravity test results is unable to meet the high-precision evaluation requirements for concealed ore bodies. Notably, recent results have demonstrated that based on the metallogenic geological characteristics of existing deposits, it is feasible to make full use of multiple geophysical survey methods (e.g., the high-precision ground magnetic survey method (HPGMS), the transient electromagnetic method (TEM), the magnetotelluric method (MT), and the controlled source audio-frequency magnetotelluric method (CSAMT)) to accurately locate and evaluate concealed ore bodies in existing metal mines [14][15][16]. While corroborating the research results for metallogenic theories, sizeable metallic ore bodies have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution by Zhang et al [1] provides an example of successful deep-seated deposit exploration, where the geological background was interpreted in combination with geophysical methods such as gravity, aeromagnetic, and controlled source audio-frequency magnetotellurics (CSAMT). The method was applied to one of the largest Ni-Cu-(PGE) deposits in the world: The Jinchuan Cu-Ni sulfide deposit in the North China Craton.…”
Section: Geophysicsmentioning
confidence: 99%